When to transfuse preterm babies. Issue 6 (24th July 2008) - Bell, E F
Abstract : The physiological anaemia experienced by preterm babies is exacerbated by common care practices such as early clamping of the umbilical cord at birth and gradual exsanguination by phlebotomy for laboratory monitoring. The need for subsequent transfusion with red blood cells can be reduced by delaying cord clamping for 30–60 s in infants who do not require immediate resuscitation. The need for transfusions can be further reduced by limiting phlebotomy losses, providing good nutrition, and using standard guidelines for transfusion based on haemoglobin or haematocrit. What those guidelines should be is not clear. Analysis of two recent large clinical trials comparing restrictive and liberal transfusion guidelines leads to several conclusions. Restrictive transfusion guidelines may reduce the number of transfusions given, but there is no reduction in donor exposures if a single-donor transfusion programme is used. There is some evidence that more liberal transfusion guidelines may help to prevent brain injury, but information on the impact of transfusion practice on long-term outcome is lacking. Until further guidance emerges, transfusion thresholds lower than those used in the two trials should not be used, as there is no evidence that lower thresholds are safe.